Intraoperative Increase of Portal Venous Pressure is an Immediate Predictor of Posthepatectomy Liver Failure After Major Hepatectomy: A Prospective Study. Issue 1 (July 2021) - Bogner, Andreas; Reissfelder, Christoph; Striebel, Fabian; Mehrabi, Arianeb; Ghamarnejad, Omid; Rahbari, Mohammad; Weitz, Jürgen; Rahbari, Nuh N.
Abstract : Objectives: The aim of this study was to assess intraoperative changes of hepatic macrohemodynamics and their association with ascites and posthepatectomy liver failure (PHLF) after major hepatectomy. Summary of Background Data: Large-scale ascites and PHLF remain clinical challenges after major hepatectomy. No study has concomitantly evaluated arterial and venous liver macrohemodynamics in patients undergoing liver resection. Methods: Portal venous pressure (PVP), portal venous flow (PVF), and hepatic arterial flow (HAF) were measured intraoperatively pre- and postresection in 67 consecutive patients with major hepatectomy (ie, resection of ≥3 liver segments). A group of 30 patients with minor hepatectomy served as controls. Liver macrohemodynamics and their intraoperative changes (ie, Δ) were analyzed as predictive biomarkers of ascites and PHLF using Fisher exact, t test, or Wilcoxon rank sum test for univariate and logistic regression for multivariate analyses. Results: Major hepatectomy increased PVP by 26.9% ( P = 0.001), markedly decreased HAF by 40.7% ( P < 0.001), and slightly decreased PVF by 13.4% ( P = 0.011). Minor resections had little effects on hepatic macrohemodynamics. There was no significant association of liver macrohemodynamics with ascites. While middle hepatic vein resection caused higher postresection PVP after right hepatectomy ( P = 0.04), the Pringle maneuver was associated with a significant PVF ( P = 0.03) and HAF reduction ( P = 0.03). Uni- and multivariate analysis revealed an intraoperative PVP increase as an independent predictor of PHLF ( P = 0.025). Conclusion: Intraoperative PVP kinetics serve as independent predictive biomarker of PHLF after major hepatectomy. These data highlight the importance to assess intraoperative dynamics rather than the pre- and postresection PVP values. Abstract : Supplemental Digital Content is available in the text